Prevalence of Eosinophilic Esophagitis and Lymphocytic Esophagitis in Adults with Esophageal Food Bolus Impaction. (28th July 2016) - Truskaite, Kotryna; Dlugosz, Aldona
Abstract : Background . The relation of esophageal food bolus impaction (FBI) to eosinophilic esophagitis (EoE) and lymphocytic esophagitis (LyE) is unclear. The aim of this study was to determine the prevalence of EoE and LyE among adults with FBI. Methods . In this retrospective study we analyzed data from all patients referred for gastroscopy during the past 5 years, because of a present or recent episode of FBI. Results . We found 238 patients with FBI (median age 51 (17–96), 71% males). Endoscopic therapy was required in 143 patients. Esophageal biopsies were obtained in 185 (78%) patients. All biopsies were assessed for numbers of eosinophils and lymphocytes. EoE was found in 18% of patients who underwent biopsy. We found 41 patients (22%) who fulfilled the criteria for both EoE and LyE (EoE/LyE). LyE was found in the 9% of patients with FBI. EoE together with EoE/LyE was the leading cause of FBI in patients ≤50 years (64%). GERD was the leading cause of FBI among patients older than 50 years (42%). Conclusions . Our study showed that EoE was the leading cause of FBI in particular among young adults. Our study highlights the need for esophageal biopsies in any patient with FBI.